Book reviews - Illman, Karl-Johan; Rian, Dagfinn; Rokem, Freddie; Harviainen, Tapani; Hansson, Svante (Nordisk judaistik/Scandinavian Jewish Studies, 1981)
Jødene og jødedommen (eds. Egil A. Wyller & Terje Gudbrandson, 1977) is reviewed by Karl-Johan Illman.Retten til å overleve (eds. Hallvard Rieber-Mohn & Leio Eitinger, 1976) is reviewed by Dagfinn Rian.Theater als Widerstand (Willmar Sauter, 1979) is reviewed by Freddie Rokem.Kuolemanlaiva S/S Hohenhörn (Elina Suominen, 1979) is reviewed by Tapani Harviainen.Mediation & assassination (Sune O. Persson, 1979) is reviewed by Svante Hansson.